Hypersensitivity to cytoskeletal antagonists demonstrates microtubule-microfilament cross-talk in the control of root elongation in Arabidopsis thaliana - Collings, David A (The New phytologist, 2006)
Elongation of diffusely expanding plant cells is thought to be mainly under the control of cortical microtubules. Drug treatments that disrupt actin microfilaments, however, can reduce elongation and induce radial swelling. To understand how microfilaments assist growth anisotropy, we explored their functional interactions with microtubules by measuring how microtubule disruption affects the sensitivity of cells to microfilament-targeted drugs. We assessed the sensitivity to actin-targeted drugs by measuring the lengths and diameters of expanding roots and by analysing microtubule and microfilament patterns in the temperature-sensitive Arabidopsis thaliana mutant microtubule organization 1 (mor1-1), along with other mutants that constitutively alter microtubule arrays. At the restrictive temperature of mor1-1, root expansion was hypersensitive to the microfilament-disrupting drugs latrunculin B and cytochalasin D, while immunofluorescence microscopy showed that low doses of latrunculin B exacerbated microtubule disruption. Root expansion studies also showed that the botero and spiral1 mutants were hypersensitive to latrunculin B. Hypersensitivity to actin-targeted drugs is a direct consequence of altered microtubule polymer status, demonstrating that cross-talk between microfilaments and microtubules is critical for regulating anisotropic cell expansion